The Importance of Age-Appropriate Poetry for Early Childhood Language and Cognitive Development: Teachers' Views on the Poem "Panca Indraku" - Fadillah, Nida Nur; Syaodih, Ernawulan (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This study investigates kindergarten teachers' perspectives on the poem "Panca Indraku" and its suitability for promoting language and cognitive development in children aged 5-6. Using qualitative methods, data were collected through interviews and online questionnaires from seven kindergarten teachers selected through purposive sampling. Based on the Miles and Huberman method, the analysis involved data collection, sorting, display, and conclusion drawing. Results indicated several challenges: limited time allocated for poetry activities, difficulty finding suitable poems, scarcity of early childhood poetry, perceptions of complexity, insufficient emphasis on reading skills, children's lack of confidence, and the complexity of language in existing poems. Nonetheless, "Panca Indraku" was favourably viewed for its simple vocabulary, appropriate structure, repetitive patterns, and alignment with cognitive development. These findings suggest that integrating age-appropriate poetry like "Panca Indraku" into early childhood education can enhance language development, cognitive skills, and imaginative exploration. The study highlights the need for more age-appropriate poetry and a curriculum that supports diverse literary forms. Limitations include a small sample size and subjective teacher perceptions. Future research should include larger samples and quantitative measures to understand poetry's impact on early childhood development comprehensively. It should explore various poetic forms and their effects on child development.